Walker Percy, Philosopher (Springer International Publishing, 2018)
Though Walker Percy is best known as a novelist, he was first and foremost a philosopher. This collection offers a sustained examination of key aspects to his more technical philosophy (primarily semiotics and the philosophy of language) as well as some of his lesser known philosophical interests, including the philosophy of place and dislocation. Contributors expound upon Percy's multifaceted philosophy, an invitation to literature and theology scholars as well as to philosophers who may not be familiar with the philosophical underpinnings of his work.